1988
DOI: 10.1177/026988118800200202
|View full text |Cite
|
Sign up to set email alerts
|

The scopolamine model of dementia: determination of central cholinomimetic effects of physostigmine on cognition and biochemical markers in man

Abstract: Administration of the muscarinic antagonist scopolamine has been proposed as a pharmacological model for Alzheimer's disease. We have attempted to characterize the cognitive deficits produced by the administration of scopolamine (0.2 and 0.4 mg intra muscularly) to normal volunteers. We have also demonstrated reversal of these deficits by the cholinesterase inhibitor physostigmine (1.2 mg intramuscularly). Physostigmine also elevated subjects' plasma ACTH levels, a marker of central cholinergic activity. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 22 publications
5
19
0
Order By: Relevance
“…c Comparison of the DTMS task accuracies achieved after 20 μg/kg scopolamine (Scop), with accuracies obtained after 50 μg/kg donepezil followed by scopolamine and with accuracies obtained after 100 μg/kg donepezil followed by scopolamine. Asterisk, significantly different from respective mean values in the vehicle (0 μg/kg) group, P<0.05. d The effect of donepezil in scopolamine-treated monkeys on shortdelay trial accuracies plotted as a function of donepezil dose 10 μg/kg dose range used in healthy human volunteers (Preston et al 1988;Molchan et al 1990;Ray et al 1992;Lines et al 1993;Snyder et al 2005). Scopolamine-induced impairment in task acquisition in the spatial memory task and in the proximate stages of memory formation, i.e., attention and vigilance, in the operant-conditioning tasks is also in keeping with similar effects reported in human subjects (Wesnes and Warburton 1984;Dunne and Hartley 1985;Preston et al 1989;Sunderland et al 1989;Duka et al 1996).…”
Section: Discussionsupporting
confidence: 76%
“…c Comparison of the DTMS task accuracies achieved after 20 μg/kg scopolamine (Scop), with accuracies obtained after 50 μg/kg donepezil followed by scopolamine and with accuracies obtained after 100 μg/kg donepezil followed by scopolamine. Asterisk, significantly different from respective mean values in the vehicle (0 μg/kg) group, P<0.05. d The effect of donepezil in scopolamine-treated monkeys on shortdelay trial accuracies plotted as a function of donepezil dose 10 μg/kg dose range used in healthy human volunteers (Preston et al 1988;Molchan et al 1990;Ray et al 1992;Lines et al 1993;Snyder et al 2005). Scopolamine-induced impairment in task acquisition in the spatial memory task and in the proximate stages of memory formation, i.e., attention and vigilance, in the operant-conditioning tasks is also in keeping with similar effects reported in human subjects (Wesnes and Warburton 1984;Dunne and Hartley 1985;Preston et al 1989;Sunderland et al 1989;Duka et al 1996).…”
Section: Discussionsupporting
confidence: 76%
“…We could obtain no evidence for antagonism of the cognitive effects of scopolamine by the benzodiazepine antagonist Ro 15-1788 or for the reversal of the effects of lorazepam by physostigmine. This pattern of results suggests that the succesful reversal of scopolamine dementia by physostigmine (Preston et al 1988b) and of lorazepam dementia by Ro 15-1788 (Preston et al 1989) were not the result of non-specific arousal. This contrasts with other data showing that such reversal can be achieved with stimulants; for example, amphetamine and caffeine may reduce the cognitive effects of scopolamine in man (Mewaldt and Ghoneim 1979;File et al 1982).…”
Section: Discussionmentioning
confidence: 70%
“…There were two important exceptions: in experiment 1 the predicted effects of scopolamine on sustained attention and verbal memory failed to reach significance. As discussed previously (Preston et al 1988b) the sensitivity of the sustained attention task seems to depend upon the context in which it occurs: if it is administered together with other tasks which require sustained concentration then it is more sensitive than if given in relative isolation. We have recently attempted to make the task more robust by running two replications of the procedure separated by other tasks in each session.…”
Section: Discussionmentioning
confidence: 87%
“…Some previous studies using scopolamine and lorazepam have attempted to dissociate these functions but have generally failed to do so [ Broks et al, 1988;Preston et al, 1988aPreston et al, ,b, 1989aWesnes et al, 1988;Braze11 et al, 19891. Others have suggested that the two processes can be at least partially psychopharmacologically differentiated [Kopelman and Corn, 1988;Curran and Birch, 19911 memory deficits are secondary to sedation therefore remains unresolved at present.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we have developed a battery of tests which have been shown to be sensitive to the sedative effects of scopolamine and lorazepam [Broks et al, 1988;Preston et al, 1988aPreston et al, ,b, 1989aBraze11 et al, 1989;Lines et al, 19911. The battery consists of computerized tests of memory, attention, and psychomotor performance, along with subjective ratings.…”
Section: Introductionmentioning
confidence: 99%